RHDM procedure for analysis of the potential specific risk due to a rockfall hazard - Đurović, Blažo; Ribičič, Mihael; Mikoš, Matjaž (Geologija, 2005)
Theoretical basis and practical legislation (Water Law and regulation acts) would allow in future the determination and classification of endangered territorial zones due to various natural hazards, among them also due to rock collapse and rockfall hazard as forms of the mass movement hazard. Interdisciplinary risk analysis, assessment and management of natural hazard are factors of harmonious spatial development in future. Especially risk analysis is the essential part of preventive mitigation actions and forms the basis for evaluation of the spatial plans, programs and policies. In accordance with the basic principles of the risk analysis the Rockfall Hazard Determination Method (RHDM) for estimation of the potential specific risk degree due to a rock fall hazard along roadways and in hinterland is introduced. The method is derived from the Rockfall Hazard Rating System (RHRS) and adjusted to a holistic concept of the risk analysis procedure. The outcomes of the phenomenon simulation with a Computer programme for rock mass movement analysis at local scale are included as well as climate and seismic conditions criteria which are newly introduced, thus making this method more adequate for specific geologic conditions in Slovenia.